Efektivitas Ekstrak Etanol Biji Alpukat (Persea americana Mill.) dalam Penurunan Hiperurisemia pada Mencit (Mus musculus L.) - Sylvia Winata; Rena Meutia; Astriani Natalia; Asyrun Alkhairi Lubis (Universitas Muhammadiyah Manado, 2025)
Hyperuricemia is a degenerative condition due to increased blood uric acid levels from purine metabolism, often occurring in the elderly. Avocado seeds (Persea americana Mill.) contain flavonoids with antioxidant and anti-inflammatory properties that can inhibit xanthine oxidation. This study evaluated the effectiveness of its extract in reducing uric acid levels in potassium bromate-induced male mice. Mice were divided into six groups: negative control (Na CMC 0.5%), positive control (allopurinol 10 mg/kg BW), three treatment groups (avocado seed extract 120, 150, and 180 mg/kg BW), and normal group. Uric acid levels were measured for seven days using one-way ANOVA test and BNT test LSD method. The results showed that doses of 120-180 mg/kg BW effectively reduced uric acid levels, with the optimal dose of 150 mg/kg BW reducing hyperuricemia by 37.3% (p = 0.118).